Tantangan dan Upaya Guru Pendidikan Agama Islam dalam Menangani Kenakalan Remaja di SMA - Karim, M.; Pohan, Muhammad Munawir; Putri, Elsa Hady (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
This study aims to analyze the efforts of Islamic Education (PAI) teachers in reducing student delinquency among adolescents at SMA Negeri 1 Kerinci. The issue of student delinquency, especially during adolescence, requires special attention from both parents and teachers, as adolescents are the future generation. PAI teachers are responsible not only for imparting knowledge but also for guiding students in understanding the difference between moral and immoral behavior, thereby preventing delinquency. This study focuses on: 1) types and causes of student delinquency, 2) efforts by PAI teachers to reduce delinquency, 3) supporting and inhibiting factors in the implementation of these efforts, and 4) the changes produced after these efforts were carried out. The method employed is descriptive qualitative research, utilizing data collection techniques that include observation, interviews, and documentation. Data analysis is conducted through reduction, presentation, verification, and conclusion. The results show that the efforts of PAI teachers in reducing student delinquency include preventive, repressive, and curative actions. These efforts include strengthening students' spirituality, enforcing school rules, religious activities, individual and group counseling, and imposing sanctions such as parent notification letters, suspensions, and even expulsion. These efforts have proven effective in reducing delinquency, as evidenced by the decreasing number of delinquency cases recorded by the school counselor (BK/BP).